2023
DOI: 10.1186/s12974-022-02680-y
|View full text |Cite
|
Sign up to set email alerts
|

Early peripheral blood gene expression associated with good and poor 90-day ischemic stroke outcomes

Abstract: Background This study identified early immune gene responses in peripheral blood associated with 90-day ischemic stroke (IS) outcomes. Methods Peripheral blood samples from the CLEAR trial IS patients at ≤ 3 h, 5 h, and 24 h after stroke were compared to vascular risk factor matched controls. Whole-transcriptome analyses identified genes and networks associated with 90-day IS outcome assessed using the modified Rankin Scale (mRS) and the NIH Stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…3 ). Our results are in validation of two small clinical studies, where elevated EN-RAGE plasma protein levels ( n = 171) [ 18 ] and S100A12 mRNA isolated from peripheral blood were associated with unfavorable 3-month functional outcome after stroke [ 19 ]. SIRT2 is an NAD + -dependent deacetylase highly expressed by both neurons and oligodendrocytes and has been implicated in regulating for instance apoptosis [ 20 ] and myelination (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…3 ). Our results are in validation of two small clinical studies, where elevated EN-RAGE plasma protein levels ( n = 171) [ 18 ] and S100A12 mRNA isolated from peripheral blood were associated with unfavorable 3-month functional outcome after stroke [ 19 ]. SIRT2 is an NAD + -dependent deacetylase highly expressed by both neurons and oligodendrocytes and has been implicated in regulating for instance apoptosis [ 20 ] and myelination (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Ren et al significantly improved stroke in mice using blood replacement and found that the total number of leukocytes and neutrophils in the blood of stroke mice was significantly reduced during and 1 h after BR treatment, and that BR treatment significantly reduced plasma levels of the pro-inflammatory cytokines IL-1β, IL-6, and TNF-α, as well as the chemokines CXCL1 and MMP-9 in stroke mice ( Ren et al, 2020 ) ( Figure 1 ). A recent clinical study has shown that poor stroke outcome modules are enriched with down-regulated B-cell-specific genes in stroke patients identified by whole-transcriptome analyses ( Amini et al, 2023 ).…”
Section: The Role Of B-cells At the Acute Phase After Strokementioning
confidence: 99%
“…Predicting functional outcomes in stroke presents a formidable challenge, largely owing to the intricate nature of the condition. [ 11 ] Consequently, we conducted a comprehensive examination of clinical peripheral blood samples extracted from stroke patients. Our objective was to uncover correlated risk factors linked to 90-day outcomes, as evaluated through the mRS.…”
Section: Introductionmentioning
confidence: 99%